A study of flow theory towards the different degree of tropical peat decomposition - Katimon, Ayob (Universiti Teknologi Malaysia, 2005)
Existing literature suggest that Darcys Law is not valid in different degree of decomposition of peat soil. The present attempts to validate the applicability of Darcys Law by comparing the velocity predicted by Darcys Law and the velocity obtained through experiment for a peat soil column. The suitability of Izbashs Law to predict the flow through peat soil column of different degree of decomposition was tested by determining the Izbashs parameter, n. Izbashs Law (v=kin) was preferred because of its continuity with the Darcys Law. Soil columns studies were set-up by applying different value in hydraulic gradient in order to obtain discharge velocity, v, of thesample. From the result, it is expected to find the suitable Izbashs parameter, n, for each depth of peat soil profile of different decomposition stage. The overall result of the study suggests that the Izbash or Power Law provides a much better approximation of water flow thorugh much deeper peat layer.